Application of Overlap Gastroduodenostomy in Billroth I Anastomosis after Totally Laparoscopic Distal Gastrectomy for Gastric Cancer. (12th August 2022) - Chen, Guojun; Li, Wenhuan; Yu, Weihua; Cen, Dong; Wang, Xianfa; Luo, Peng; Yan, Jiafei; Chen, Guofu; Zhu, Yiping; Zhu, Linhua
Abstract : Delta-shaped gastroduodenostomy (DSGD) and overlap gastroduodenostomy (OGD) are the two most widely used intracorporeal Billroth I anastomosis methods after distal gastrectomy. In this study, we compared the short-term outcomes of DSGD and OGD in total laparoscopic distal gastrectomy (TLDG). In a retrospective cohort study, we examined 92 gastric cancer patients who underwent TLDG performed by the same surgeon between January 2014 and June 2018. All patients underwent Billroth I reconstruction (OGD, n = 45; DSGD, n = 47) and D2 lymph node dissection. We retrospectively reviewed the surgical outcomes, clinical pathological results, and endoscopy results. Laparoscopic surgery was successfully performed in both groups without conversion to open surgery. The demographic and clinical characteristics were similar between the two groups (P > 0.05 ). There were no significant differences between the two groups in operation time (158.9 ± 13.6 min vs. 158.8 ± 14.8 min, P = 0.955 ), anastomotic time (19.4 ± 3.0 min vs. 18.8 ± 2.9 min, P = 0.354 ), intraoperative blood loss (88.9 ± 25.4 mL vs. 83.7 ± 24.3 mL, P = 0.321 ), number of lymph node dissections (31.0 ± 7.1 vs. 29.2 ± 7.5, P = 0.229 ), length of hospital stay (8.8 ± 2.7 days vs. 9.1 ± 3.0 days, P = 0.636 ), fluid intake time (3.1 ± 0.7 days vs. 3.2 ± 0.7 days, P = 0.914 ), and morbidity of postoperative complications (6.7% [3/45] vs. 10.6% [5/47], P = 0.499 ). Endoscopy performed 6 months postoperatively showed that the residual food (P = 0.033 ), gastritis (P = 0.029 ), and bile (P = 0.022 ) classification score significantly decreased in the OGD group, and there were no significant differences 12 months postoperatively. OGD is a safe and effective reconstruction technique with comparable postoperative surgical outcomes and endoscopy results when compared with those of DSGD.